Analysis of Factors Causing Deterioration in Patients with Head Trauma - I Made Suindrayasa; Hendry Irawan; Meril Valentine Manangkot (Indonesian Journal of Global Health Research, 2026)
The incidence of head trauma continues to increase from year to year and causes death or disability in adults. Factors that cause deterioration in patients with head trauma are age, initial Glasgow Coma Scale (GCS), RTS (Revised Trauma Score), blood pressure, travel time to hospital (RS), and other organ trauma. Deterioration in head trauma patients can be seen from the Glasgow Outcome Scale (GOS). The problem formulation in this study is how the factors that cause deterioration in patients with head trauma are related. The purpose of this study is to describe the relationship between factors that cause deterioration in patients with head trauma and find the dominant factor. This research method is comparative analytic with a cross-sectional design. Respondents were selected using purposive sampling with a total of 48 respondents. Data on GOS, age, GCS, RTS, and blood pressure were collected from patient medical records. Data on travel time to hospital were collected from interviews with patients' families. The obtained data were subjected to multivariate analysis using logistic regression tests. The results showed that the variables of age, GCS, RTC, blood pressure, and travel time to hospital have a relationship with the GOS variable (p-value <0.005). The results of a multivariate logistic regression analysis showed that the most dominant factor influencing the worsening of severe head injury (GOS) was the RTC value (OR:16.18). In conclusion, a lower RTC value indicates a worse prognosis for head injury patients.